"You might as well just all agree with each other:"An initial study of cyberbullying victims' social presence in online discussions. (July 2021) - Byrne, Virginia L.
Abstract: Cyberbullying affects the majority of undergraduate women, contributing to withdrawal from social media and chilling their participation in the growing world of collaborative online discussions. This pilot mixed-methods study integrates surveys, observations, and interviews of nine undergraduate women at a Mid-Atlantic research university to investigate how the chilling effect of cyberbullying may extend into peer interactions within an increasingly common online instructional practice: online discussion boards. It is observed that, in comparison to their non-victimized peers, participating women with prior cyberbullying experiences enact lower social presence and adopt self-silencing and conflict avoidant coping strategies. In particular, these women avoid ever disagreeing with peers out of fear of starting "drama." Findings challenge educators to consider the potential unintended consequences of instructional design choices and contributes to our understanding of how to design more equitable online learning environments for today's socially networked learners. Highlights: Mixed methods pilot study of undergraduate women with cyberbullying experiences. Women who were cyberbullied enact lower social presence on discussion boards. Cyberbullied women may self-censor on discussion boards for fear of backlash.